2015
DOI: 10.1097/acm.0000000000000734
|View full text |Cite
|
Sign up to set email alerts
|

Learn, See, Practice, Prove, Do, Maintain

Abstract: Acquisition of competency in procedural skills is a fundamental goal of medical training. In this Perspective, the authors propose an evidence-based pedagogical framework for procedural skill training. The framework was developed based on a review of the literature using a critical synthesis approach and builds on earlier models of procedural skill training in medicine. The authors begin by describing the fundamentals of procedural skill development. Then, a six-step pedagogical framework for procedural skills… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(142 citation statements)
references
References 68 publications
2
115
0
Order By: Relevance
“…The 7th edition NRP educational curriculum follows an evidence-based framework known as the “Learn-See-Practice- Prove-Do-Maintain” (LSPPDM) pedagogy 8. The LSPPDM pedagogy is a six-phase framework for teaching procedural skills, assessing competency, and maintaining competency once acquired.…”
Section: Advances In Trainingmentioning
confidence: 99%
“…The 7th edition NRP educational curriculum follows an evidence-based framework known as the “Learn-See-Practice- Prove-Do-Maintain” (LSPPDM) pedagogy 8. The LSPPDM pedagogy is a six-phase framework for teaching procedural skills, assessing competency, and maintaining competency once acquired.…”
Section: Advances In Trainingmentioning
confidence: 99%
“…In one study, pediatric residents who received simulation-based education were more successful in peripheral intravenous catheter placement and lumbar puncture than those taught with other methods [10]. Modern procedural training paradigms leverage simulation as the primary educational method [11]. Indeed, the standard practice of “see one, do one, teach one” may eventually evolve into “see one, simulate many, do one competently, and teach everyone” [12].…”
Section: Discussionmentioning
confidence: 99%
“…Only one CCE used the widely accepted and commonly used medical education term of an evidence-based approach, when describing this domain [ 37 ]. There is substantive research surrounding this approach to learning and professional development [ 38 ]. Recent research found that 46 % of USA chiropractors did not take evidence-based practice into account when making clinical decisions [ 39 ].…”
Section: Discussionmentioning
confidence: 99%